2009
DOI: 10.1177/0022022108330987
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Acculturation for Immigrant Women From the Former Soviet Union

Abstract: Most research on immigrant acculturation has been conducted with cross-sectional samples, using statistical designs that may not capture different trajectories for the components that contribute to this complex concept. The purpose of this study was to examine change over time in acculturation for 226 women from the former Soviet Union who had lived in the US fewer than eight years when recruited. Using self-report data from four annual waves, growth trajectories were examined in four components of acculturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
1
21
2
Order By: Relevance
“…In these analyses we used two different scoring methods to overcome some of the limitations of the unidimensional approach; however, additional prospective investigations that permit a more thorough examination of uni- and multidimensional approaches are needed. Miller and colleagues (2009) found linear increases in American behaviors but curvilinear decreases in Russian behaviors in their longitudinal study of immigrant women from the former Soviet Union. However, this is the only study to our knowledge specifically assessing changes in acculturation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In these analyses we used two different scoring methods to overcome some of the limitations of the unidimensional approach; however, additional prospective investigations that permit a more thorough examination of uni- and multidimensional approaches are needed. Miller and colleagues (2009) found linear increases in American behaviors but curvilinear decreases in Russian behaviors in their longitudinal study of immigrant women from the former Soviet Union. However, this is the only study to our knowledge specifically assessing changes in acculturation.…”
Section: Discussionmentioning
confidence: 94%
“…psychological distress, acculturation-based conflict). In a review of the literature, only one study was found that focused on a direct test of whether there were changes in acculturation over time (Miller, Wang, Szalacha, & Sorokin, 2009). Miller and colleagues (2009) found varying levels of change for adult immigrant women from the former Soviet Union across different aspects of acculturation (American behavior, Russian behavior, English language proficiency, and cultural generativity) over a 4-year period.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated the importance of considering host and heritage cultural dimensions independently, as well as measuring language, identity, and behavior as separate components to predict behavior and mental health, as they may have different developmental trajectories (Birman & Trickett, 2001; Miller, Wang, Szalacha, & Sorokin, in review; Ryder, Alden, & Paulhus, 2000). Furthermore, recent research has highlighted the importance of understanding acculturation as a transactional variable between individuals and their environment.…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al, 1995;Rogers & Ward, 1993), as well as changes in acculturation behaviour over time (e.g. Miller, Wang, Szalacha & Sorokin, 2009).…”
Section: Fitnessmentioning
confidence: 99%
“…A particularly strong feature of the study was the four-year longitudinal design. Employing multilevel modelling of results, Miller et al, (2009) found that each acculturation component changed at a varied rate, following different shapes and directions. They concluded that acculturation consists of myriad complex components, which change differently over time and thus should be measured separately.…”
Section: Length Of Residencementioning
confidence: 99%